The Effect of Temperature over the Growth and Biofilm Formation of the Thermotolerant Aspergillus flavus - José Alejandro Hernández-Benítez; Brenda Nallely Santos-Ocampo; Daniel Genaro Rosas-Ramírez; Luis Antonio Bautista-Hernández; Víctor Manuel Bautista-de Lucio; Néstor Octavio Pérez; Aída Verónica Rodríguez-Tovar (Journal of Fungi)
Aspergillus flavus is a medically relevant fungus, particularly in tropical regions. Although its aflatoxin production and thermotolerance are well documented, its biofilm-forming ability has received less attention, despite being a key factor in the virulence of A. flavus as an opportunistic pathogen, which can significantly impact therapeutic outcomes. To investigate the influence of temperature on the growth and biofilm formation of an A. flavus isolate, we compared it on solid media with the reference strain A. flavus ATCC 22546 and documented morphological changes during conidial germination. We examined biofilm formation in both strains across different temperatures and evaluated the susceptibility of this A. flavus isolate to antifungal agents in both planktonic and biofilm form. Our results showed that the temperature can promote conidiation on solid media. Radial growth was highest at 28 °C, while the conidial count and density were favored at higher temperatures. Moreover, we determined that 37 °C was the optimal temperature for conidial germination and biofilm formation. We described four distinct phases in A. flavus biofilm development—initiation (0–12 h), consolidation (12–24 h), maturation (24–48 h), and dispersion (48–72 h)—with the notable presence of conidial heads at 42 °C. Carbohydrates and proteins constitute the primary components of the extracellular matrix. We observed an abundance of lipid droplets within the hyphae of the MMe18 strain biofilm. The mature biofilms demonstrated reduced susceptibility to amphotericin B and itraconazole, requiring higher inhibitory concentrations for both antifungals compared with their planktonic counterparts.